From 'beasts of burden' to 'backbone of society': The fiscal forging of a new Bolivian middle class. (December 2022) - Sheild Johansson, Miranda
The recently re-branded and highly digitalised Bolivian Tax Office, Servicio de Impuestos Nacionales (SIN), works to consolidate various socio-economic groups, such as the Aymara bourgeoisie (wealthy traders who identify as all or part indigenous), into a new middle class. SIN's motivations to do so are bound up in broader international financial logics where the development of an archetypal European middle class – the so-called backbone of society – is considered key to a healthy tax profile. The efforts to forge a new middle class involves the deliberate projection of SIN as an accountable, effective, and 'modern' organisation, with the aim of promoting a broader fiscal culture that embodies these same characteristics; targeted education of the populace about taxpaying as an ethical act in line with highland indigenous values; and, policy-making that encourages income tax over VAT (value-added tax). However, these new middle classes experience the temporality and individualising effects of SIN's system as incompatible with the money flows and values of their own economic lives. Specific areas of contention include the rhythms of incomes and the ethics of risk- and profit-sharing. In exploring this incompatibility, I argue that fiscal systems are key to the production and imaginations of middle-classness, both as they succeed and fail.